Oblique Du-Fort Frankel Beam Propagation Method. (5th August 2010) - Chan, Ken; Sewell, Philip; Vukovic, Ana; Benson, Trevor
Abstract : The oblique BPM based on the Du-Fort Frankel method is presented. The paper demonstrates the accuracy and the computational improvements of the scheme compared to the oblique BPM based on Crank-Nicholson (CN) scheme.